APPLICATION OF ERA’S METHOD FOR THE EXPERIMENTAL MODAL ANALYSIS OF COMPOSITE STRUCTURES - Silva, Lorraine Aparecida; Zambolini-Vicente, Bruno Gabriel Gustavo Leonardo Zambolini; Lima, Antônio Marcos Gonçalves de (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This work is placed on the scope of characterization and modeling of structures and the central objective is to establish a computer code capable to provide models for structures of interest from practical experimentation, to be used to refine the computer models a posteriori. To realize that project, the experimental modal analysis was applied in the Eigensystem Realization Algorithm ”“ ERA. As well as most of the techniques of identification of dynamic of systems, the ERA also creates the compute modes, being necessary the application of procedures for filtering the real modes before the noises and/or computers modes. In this work, two techniques for the distinction were used: Modal Amplitude Coherence (MAC) and Modal Singular Value (MSV). Beside this, a novel approach to help interpret and filter based in MSV deviation was proposed and tested, producing good results. To achieve this, a computer code that receives experimental data and returns the global properties of the system, i.e., the natural frequencies, the damping factors and the mode shapes was developed. The preliminary results, developed in the know structure, indicate the code has the potential to handle with complex geometries.